Analisis Efektivitas, Laju Pertumbuhan, Kontribusi PBB-P2, Forecasting Terhadap Pendapatan Asli Daerah Kabupaten Karawang - Sari, Eko Gumaya; Sulastri, Lilis; Fajriah, Anisa Nur (Universitas 17 Agustus 1945 Jakarta, 2023)
The aim of this research is to analyze and predict results after implementing Regional Regulation no. 15 of 2021 concerning the authority to collect PBB-P2 by regional governments. The method used is a quantitative method which is a form of research carried out systematically, structured and detailed. The research results show that the effectiveness level of PBB-P2 is on average effective, the growth rate value increases, while the contribution value of PBB-P2 is considered less than optimal. Based on PBB-P2 forecasting for 2023, it is estimated that there will be an increase of 26.70%. The policy of the Regional Government of Karawang Regency to increase the NJOP PBB-P2 as regulated in Regional Regulation No. 15 of 2021 can be said to be appropriate, because the value of effectiveness, contribution and growth rate of PBB-P2 has a positive impact, in line with the PBB-P2 forecasting for 2023. In general This will automatically help accelerate national economic recovery, especially after the new normal era.